2014
DOI: 10.5194/isprsarchives-xl-8-885-2014
|View full text |Cite
|
Sign up to set email alerts
|

Satellite based remote sensing technique as a tool for real time monitoring of leaf retention in natural rubber plantations affected by abnormal leaf fall disease

Abstract: Most parts of the traditional natural rubber growing regions of India, extending from Kanyakumari district of Tamil Nadu in the South to Kasaragod district of Kerala in the North received excess and prolonged rains during 2013. This led to severe incidence of Abnormal Leaf Fall (ALF) disease caused by the fungus, <i>Phytophthora</i> sp. The present study demonstrated the first time use of satellite remote sensing technique to monitor ALF disease by estimating Leaf Area Index (LAI) in natural rubber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Remote sensing tools based on satellites are becoming increasingly useful in diagnosing and inspecting drought in a range of yield . [4]). Dreadful dryness during the sunny season drastically lowers natural rubber development and yield, this study calculate the spatial parameters of stress in agricultural drought in latex tree colony in Tamilnadu south state Kanyakumari and Kerala.…”
Section: Modis Terra Satellite Data For Assessing Agricultural Drough...mentioning
confidence: 99%
“…Remote sensing tools based on satellites are becoming increasingly useful in diagnosing and inspecting drought in a range of yield . [4]). Dreadful dryness during the sunny season drastically lowers natural rubber development and yield, this study calculate the spatial parameters of stress in agricultural drought in latex tree colony in Tamilnadu south state Kanyakumari and Kerala.…”
Section: Modis Terra Satellite Data For Assessing Agricultural Drough...mentioning
confidence: 99%
“…A possible explanation could be that such studies are limited by the occurrence of the disease, which can be infrequent, and the scale of the incident, which needs to be large enough to be detected by satellite images. One document [15] had used satellite images to monitor Phytophthora leaf disease, which is caused by fungus. Interestingly, the study demonstrated that remote sensing techniques can facilitate the detection of leaf disease.…”
Section: Application Categoriesmentioning
confidence: 99%
“…Two platforms were observed to obtain data for the detection, mapping and investigation of disease outbreaks in rubber: Satellite and UAV as in Table 9. Two studies [15,143] used satellite imagery to detect and monitor leaf diseases at plantation level. Ranganath et al [143] used multi-date imagery from the IRS satellite to evaluate its potential for detecting and monitoring the outbreak of Corynespora and Gloeosporium fungi in rubber plantations in the south of India.…”
Section: Disease Detectionmentioning
confidence: 99%
See 2 more Smart Citations